Penatalaksanaan fisioterapi pada stiffness elbow joint post. Orif epicondylus lateral sinistra di rsud dr. Moewardi surakarta - Trio Firmanila, Hendra, Dwi Rosella K, S.Fis,M.Fis (2016)
Background: Stiffness Elbow Joint is a condition with fibration and oedema in the capsule ligaments and muscles around the joints because of adhesions in the soft tissues of each other. This condition will worsen if prolonged immobilization and joint ligament retained in the shortest position. Physiotherapy service on condition Stiffness Elbow Joint Sinistra is to maintain and restore movement of the body functions manually or with equipment. Purpose : To investigate the implementation of physiotherapy in reducing pain, increasing range of motion, increase muscle strength and improve functional activity in conditions Stiffness joint of Elbow sinistra modalities using Infra Red (IR) and Exercise Therapy (TL). Results: After treatment for 6 times the therapeutic results obtained pain assessment silent T1: 1 to T6: 1, push pain T1: 1 to T6: 1, movement pain T1: 4 to T6: 3, increased range of motion elbow, active movement T1: S (0-0-90 °) becomes Q6: S (0-0-95 °), increase muscle strength Elbow Flexor Sinistra T1: 3 to T6: 4, Elbow extensor Sinistra T1: 4 to T6: 5, increasing the value of the activity of functional abilities when dressing (upper limb) T1: 5, became T6: 6. Conclusion:Infra Red radiation can reduce pain in Elbow Joint stiffness Sinistra. Exercise therapy can increase the range of motion and increase muscle strength in Elbow Joint stiffness Sinistra